Causality between energy consumption, gross domestic product, carbon dioxide emissions and employment in Indonesia, Malaysia and Thailand - Wong, Siew Wei (Universiti Malaysia Sarawak, 2011)
This study examines the causality between energy consumption, gross domestic product, carbon dioxide emissions and employment in Indonesia, Malaysia and Thailand over the period 1980 to 2008. The Augmented Dickey-Fuller (ADF), Phillips-Perron (PP) and Kwiatkoski-Phillips-Schmidt-Shin (KPSS) Unit Root Tests, Johansen and Juselius Cointegration Test, Normalized Equation, Error Correction Model and the Wald Test are conducted in this study.